Efecto de dosis de bioestimulante tetrahormonal en el cultivo de Cebolla China (Allium Fistulosum) en la provincia de Lamas - Del Águila López, Evelyn Janny (2012)
This research paper entitled "Effect of dose tetrahormonal biostimulant in growing Chinese onion (Allium fistulosum) in the province of Lamas", had the following objectives: Evaluate and analyze the effect of five doses of Biostimulant Tetrahormonal Biogyz in production onion crop of China (Allium fistulosum), variety the Red, determine the appropriate dose for Biogyz Tetrahormonal Biostimulant growing China onion vari ety Red Perform the economic analysis of the treatments. Established in Fundo Horticultural "The Pacific" in the district and province of Lamas, was used for the statistical design of randomized complete block design (RCBD) with six treatments and three replicates and treatments were studied Biogyz Dose: To = Control; T1 = 100 cc.ha-1, T2 = 150 cc.ha-1, T3 = 200 cc.ha-1, T4 = 250 cc.ha-1 and T5 = 300 cc.ha-1. The most significant findings were that treatments based on applied biostimulant Biogyz terahormonal induced responses in plant fresh weight (cm), stem diameter (cm) and total number of leaves per plant, the same as promoting growth and development structure of the plant, resulting in higher yields in the culture of China Onion, Red variety, treatment 3 (200 cc.ha- 1) with Tetrahormonal Biostimulant Biogyz showed the highest average yield of fresh weight with 39.86 ton.ha-1 and consequently obtained the best cost / benefit ratio with 4.12 and the highest net benefit to S /. 9916.64 soles, exceeding the control treatment in 47.6%. All treatments studied wealth being generated treatment T0 (control) which showed the lowest Benefit / cost to 2.16.